Investigating kinetic behavior and reaction mechanism on autothermal pyrolysis of polyethylene plastic. (15th April 2023) - Xie, Wen; Su, Jing; Zhang, Xiangkun; Li, Tan; Wang, Cong; Yuan, Xiangzhou; Wang, Kaige
Abstract: To reduce the energy supply for pyrolysis, autothermal pyrolysis is one of the most promising approaches to upcycle plastic waste. In this work, both single-step and multi-step methods were applied to perform kinetic studies of low-density polyethylene (LDPE) pyrolysis under oxidative atmospheres (0, 5, and 10% O2 balanced by N2 ) by changing the heating rate from 5 to 20 K min −1 . Miura integral method was then used to estimate the apparent activation energy. The major findings showed that the multi-step method using asymmetric double sigmoidal (Asym2Sig) deconvolution procedure was more appropriate to study kinetic behaviors of LDPE autothermal pyrolysis. The activation energy needed for LDPE pyrolysis under N2 was 271 kJ·mol −1, while the activation energies of the three pseudo-reactions under 5% O2 were 71, 153 and 189 kJ·mol −1, and under 10% O2 were 74, 224 and 169 kJ·mol −1, indicating that LDPE autothermal pyrolysis was more energy-saving than conventional LDPE pyrolysis. Additionally, the reaction mechanism was proposed to provide an accurate and critical guideline for commercializing this novel technical route, which is beneficial to achieving sustainable plastic waste management and mitigating plastic pollution, simultaneously. Graphical abstract: Image 1 Highlights: Kinetics of LDPE autothermal pyrolysis was investigated using Miura method. Asym2Sig deconvolution function is used to divide stages of pyrolysis reaction. E 0 (kJ·mol −1 ) for autothermal pyrolysis (<225) is lower than that under N2 (271).